Selected dietary habits of academic youth – students of Sanok high school - Smoleń, Ewa (Polish Journal of Public Health, 2013)
Introduction. Nutrition and diet are significant elements of health behaviour determining health status. Dietary habits result from social and economical conditions, which are responsible for specific health behaviour and the choice of a particular dietary model. Normal health status is determined by 24-hour meal plan as well as quality and quantity of nutritional components. The Committee on Human Nutrition of Polish Academy of Science, the Institute of Food and Nutrition, and Polish Society of Nutritional Sciences elaborated dietary recommendations for general population in Poland. When acting according to these guidelines, the organism is provided with all necessary nutritional components and the most frequent dietary mistakes of young Poles can be avoided.Aim. Assessment of selected dietary habits of Grodek State Vocational High School in Sanok.Material and methods. The study included 194 students of Higher State Vocational School. The participation in the study was voluntary and anonymous. A survey questionnaire, developed by the author, assessed 24-hour plan of meals and their quality as well as students’ compliance with the principles of rational nutrition. Outcomes were analysed statistically using the chi-square test of independence.Conclusions. The majority of respondents had at least three or four meals a day. More than half of the study group declared they had breakfast every day, and for most students it was the most important meal in their daily menu. Every second student living in the city or country had a two-course dinner whereas significantly smaller number of rural inhabitants participating in the study declared so. The most frequent dietary mistakes included consuming sweets between meals, frequent drinking of coffee, excessive consumption of meat, especially by men, and a rare consumption of fish.Results. The determination of dietary mistakes among students allows correcting them by adequate preventive actions.